2008
DOI: 10.1002/ejoc.200800598
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Binaphthophosphepine‐Promoted [3+2] Annulations of N‐Ts‐ and N‐DPP‐Imines with Allenoates and 2‐Butynoates

Abstract: The use of binaphthophosphepine 1a as a catalyst for the [3+2] cyclisation between allenoates or 2-butynoates and imines was investigated. The effects of the imine protecting group on both the catalytic activity and enantioselectivity were determined by comparing the behaviour of N-tosyland N-DPP-imines. The N-DPP-imines displayed lower reac-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(25 citation statements)
references
References 26 publications
(15 reference statements)
0
25
0
Order By: Relevance
“…The same phosphine had been described previously to furnish high enantiomeric excesses in [3+2] cyclizations between allenoates and either enones 6b or imines, 16 as well as in [4+2] cyclizations on imines. 4 To further investigate the scope of the asymmetric cyclization methodology involving Binepine (S)-4 as the catalyst, we examined the possibility of using olefins with either esters or cyano and ester groups as electron-withdrawing functions (Scheme 3).…”
Section: Resultsmentioning
confidence: 90%
“…The same phosphine had been described previously to furnish high enantiomeric excesses in [3+2] cyclizations between allenoates and either enones 6b or imines, 16 as well as in [4+2] cyclizations on imines. 4 To further investigate the scope of the asymmetric cyclization methodology involving Binepine (S)-4 as the catalyst, we examined the possibility of using olefins with either esters or cyano and ester groups as electron-withdrawing functions (Scheme 3).…”
Section: Resultsmentioning
confidence: 90%
“…Moreover, the experimental conditions were very mild and the reaction times were very short. 104 The yields were good or moderate but lower than ones obtained from Ntosylimines. That was due to partial decomposition during the isolation by column chromatography.…”
Section: [3d2] and [4d2] Cycloaddition Catalyzed By Phosphinesmentioning
confidence: 91%
“…The authors also studied the reaction of both N-DPP (208) 104 and N-tosylimines (202), 105 catalyzed by a chiral phosphine derivative 210 (Scheme 90). The reported data demonstrated that the N-DPP group afforded higher enantiomeric excesses than the Ntosyl group; however the yields were higher with the latter one.…”
Section: [3d2] and [4d2] Cycloaddition Catalyzed By Phosphinesmentioning
confidence: 99%
“…The aliphatic derivatives are not stable; as a rule, they are involved in the reaction without puri fication. The standard procedure for the removal of the Dpp fragment is acid solvolysis (a) on heating in concentrated HCl [60], (b) at ambient temperature in aqueous alcoholic solution of HCl [62,63], or (c) by treatment with gaseous HCl [61]. Yields vary from moderate to high.…”
Section: N Phosphinoyl Imines (Iii)mentioning
confidence: 99%